FAKTOR - FAKTOR YANG MEMPENGARUHI UNDERPRICING PADA SAHAM SAAT INITIAL PUBLIC OFFERING (IPO) - Devi, Grace; Salim, Susanto (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze empirically the factors that influence the level of underpricing that occurs in non-primary consumer goods sector companies carrying out an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. A total of 38 samples were taken by purposive sampling technique. The independent variables used are underwriter reputation, firm size, board size and profitability. The processing technique for data is using multiple regression analysis with Eviews 12 program. The outcomes from this study indicate that the underwriter's reputation variable has a negative direction and has a significant effect on underpricing. Firm size and board size variables have a positive and insignificant relationship to underpricing, while the profitability variable has a negative and insignificant relationship to underpricing. The implication from this research is the need to choose underwriters with a good reputation so that they can perform their role optimally as intermediaries between issuers and investors and offers that occur benefit each party.